Demographic Characteristics and Locus of Control Associated with Employee Burnout - Fani Amalia Kusumadewi; Indriati Paskarini; Aina Mumtaazah Khairunnisa (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Burnout in employees is caused by individual factors, including demographic characteristics and locus of control. This study aimed to analyze the relationship between demographic characteristics and locus of control with burnout among employees at the head office of a pharmaceutical company in North Jakarta. Methods: This research was a correlational study with a cross-sectional design. The population in this research were permanent employees of the pharmaceutical company's head office in North Jakarta, amounting to 88 employees. The research sample was 47 employees, using the probability sampling method with the proportional stratified random sampling technique. The independent variables in this research were gender, age, education level, marital status, and locus of control. At the same time, the dependent variable in this research was burnout. Data collection used the Maslach Burnout Inventory (MBI) and Work Locus of Control (WLOC). The data in this study were analyzed by the Spearman Correlation test and the Cramer Correlation test. Results: Most of the employees were female, 26-35 years old, married, and have a college education level. Burnout was moderate in most of these employees. Demographic characteristics which had a relationship with burnout were age (p=0.012) and education level (p=0.014). Meanwhile, gender (p=0.373) and marital status (p=0.297) had no relationship with burnout. Locus of control and burnout also had a relationship (p=0.015). Conclusion: Gender and marital status had no relationship with employees burnout. However, age and education level had a relationship with employees burnout. There was also a relationship between locus of control and burnout.